2020
DOI: 10.1021/acsmacrolett.0c00236
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Dynamics in Block Copolymer Electrolytes Detected by Neutron Spin Echo

Abstract: Polymer chain dynamics of a nanostructured block copolymer electrolyte, polystyrene-block-poly(ethylene oxide) (SEO) mixed with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt, are investigated by neutron spinecho spectroscopy on the 0.1-100 ns timescale and analyzed using the Rouse model at short times (t ≤ 10 ns) and the reptation tube model at long times (t ≥50 ns). In the Rouse regime, the monomeric friction coefficient increases with increasing salt concentration as seen previously in homopolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The reduced local chain stretching of the normal-tapered PS-b-POEM also can make it more robust toward concentration polarization effects in a battery environment, in which an electrolyte with an initial ion concentration of [Li + ]/[EO] ∼ 0.05 may experience a concentration gradient of 0 < [Li + ]/ [EO] < 0.1 during concentration polarization. 82 Minimal domain spacing variance can enable the electrolyte to maintain its initial morphology, transport properties, and sufficient contact with the battery electrodes. Another method to quantify chain stretching is the calculation of the statistical segment length of POEM, b POEM , as shown in Figure S9b.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The reduced local chain stretching of the normal-tapered PS-b-POEM also can make it more robust toward concentration polarization effects in a battery environment, in which an electrolyte with an initial ion concentration of [Li + ]/[EO] ∼ 0.05 may experience a concentration gradient of 0 < [Li + ]/ [EO] < 0.1 during concentration polarization. 82 Minimal domain spacing variance can enable the electrolyte to maintain its initial morphology, transport properties, and sufficient contact with the battery electrodes. Another method to quantify chain stretching is the calculation of the statistical segment length of POEM, b POEM , as shown in Figure S9b.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The self-diffusion constant of ions in polymer electrolytes has been extensively studied as it can be directly obtained from experiments through pulsed field-gradient nuclear magnetic resonance and is easily calculated from equilibrium simulations . It is typically found that ion diffusion is strongly coupled with the polymer segmental relaxation rate (related to the glass transition temperature T g ) as the local friction ions experience is mainly controlled by the relaxation of polymers. Thus, a major strategy to improve overall conductivity has been to increase polymer segmental mobility (or reduce T g ).…”
Section: Introductionmentioning
confidence: 99%
“…Energy generation and storage in an LIB depend, in part, on the flux of lithium ions across the electrolyte, and several factors (e.g., polymer/ion chemistry, ion concentration) govern this lithium-ion transport. For example, the ratio of lithium ions, [Li + ], relative to ethylene oxide units, [EO], can modulate ion solvation by the polymer, chain stretching/stiffness, and transient ion–polymer cross-linking . Thus, knowledge of local ion concentrations within a conducting domain becomes increasingly important for BP electrolytes, in which the presence of domain interfaces can create heterogeneities in the ion transport.…”
Section: Effects Of Synthesis and Formulation Variables On Intra-doma...mentioning
confidence: 99%